Xenodon guentheri Boulenger 1894 (SQUAMATA, DIPSADIDAE): NEW STATE RECORD AND KEY TO THE GENUS Xenodon IN THE STATE OF RIO GRANDE DO SUL, SOUTHERN BRAZIL - Diesel Abegg, Arthur; Lucchesi Balestrin, Rafael; Schossler, Martin; Toso, Javier; Rohling Ghizoni- Jr, Ivo (Boletín de la Sociedad Zoológica del Uruguay, 2017)
The dipsadid snake, Xenodon guentheri, endemic to Brazil, was recorded for the first time in the state of Rio Grande do Sul. Two specimens were found in São José dos Ausentes on 12 May 2014 and 14 April 2016. We reviewed the records of X. guentheri in scientific collections and a map was generated with the points of occurrence of the species throughout its distribution range. In addition, we also present a dichotomous key to identify species of the genus Xenodon in the State of Rio Grande do Sul.